Concentrations and sources of Cd, Cr, Cu, Fe, Ni, Pb and Zn in soil of the Mitidja plain, Algeria - Laribi, Abdelkader; Shand, Charles; Wendler, Renate; Mouhouche, Brahim; Colinet, Gilles (Toxicological and environmental chemistry, 2019)
In the last few decades, the Mitidja plain has undergone economic development which may have altered the concentrations of some trace metals in its soils. Therefore, this study was aimed at investigating the concentrations and sources of Cd, Cr, Cu, Fe, Ni, Pb and Zn in 180 composite topsoil samples using a combination of environmental quality indicators and multivariate statistical approaches with a geographic information system (GIS). Based on spatial distribution maps, various hot-spots have been identified. Enrichment factors (EFs) indicated that Cd, Cu, Pb and Zn were from anthropogenic sources, while Ni and Cr were controlled mainly by natural lithogenic source. Multivariate statistical analyses were in agreement, except for Cu which was classified as coming from both anthropogenic and lithogenic sources.